Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.5142/jgr.2011.35.2.209
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method for the Preparation of Crude Gintonin from Ginseng Root, Stem, and Leaf

Abstract: Ginseng has been used as a general tonic agent to invigorate the human body as an adaptogenic agent. In a previous report, we have shown that ginseng contains a novel glycolipoprotein called gintonin. The main function of gintonin is to transiently enhance intracellular free Ca2+ [Ca2+]i levels in animal cells. The previous method for gintonin isolation included multiple steps using organic solvents. In the present report, we developed a simple method for the preparation of crude gintonin from ginseng root as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 8 publications
0
39
0
Order By: Relevance
“…In previous studies we demonstrated that gintonin induced CaCC activation in Xenopus oocytes through the mobilization of [Ca 2+ ] i [5,6]. When we compared the potency for endogenous CaCC activation in Xenopus oocytes with the previously acquired extract, we found that ethanol gintonin was not much different from that of previous gintonin for the activation of CaCC.…”
Section: Resultsmentioning
confidence: 70%
See 4 more Smart Citations
“…In previous studies we demonstrated that gintonin induced CaCC activation in Xenopus oocytes through the mobilization of [Ca 2+ ] i [5,6]. When we compared the potency for endogenous CaCC activation in Xenopus oocytes with the previously acquired extract, we found that ethanol gintonin was not much different from that of previous gintonin for the activation of CaCC.…”
Section: Resultsmentioning
confidence: 70%
“…We demonstrated that active agents that caused CaCC activation in Xenopus oocytes and transiently elevated the intracellular calcium concentration ([Ca 2+ ] i ) in mammalian cells are not ginsenosides but gintonin [5]. In addition, we found that the ginseng stem and leaf also contain gintonin [6]. Thus, we provided the evidence that ginseng contains novel ingredients and that one novel ingredient, gintonin, could also be the main agent for Ca 2+ -mediated various cellular events.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations